Sustentabilidade empresarial, inovação e desempenho econômico: evidências para empresas da América Latina, brasileiras, do Triângulo Mineiro e Alto Paranaíba - Barbosa, Ismael (2024)
Objective: The objective of this study was to investigate how the relationship between corporate sustainability, innovation, and regional context influences the economic performance of companies located in Latin America, Brazil, and the Triângulo Mineiro and Alto Paranaíba regions. Method: To achieve this goal, the thesis was structured into three articles. Article 1 conducted a systematic literature review, Article 2 performed panel data regression, and Article 3 also conducted panel data regression. Results: In Article 1, recent innovation theoretical models, such as the network and systemic models, proved effective in understanding regional innovation. However, there is a lack of attention to the regional impacts of innovation and limited exploration of regional aspects. It is necessary to align studies with appropriate theoretical models to better understand innovation in regional contexts, aiming at the economic and social development of regions. Article 2 results showed a lack of consistent evidence regarding the superior economic performance of companies investing in sustainability and innovation. This may be attributed to the time required for such investments to generate tangible financial results, as indicated by ROA and ROE indices, as well as market pricing, evidenced by market-to-book value and Q-Tobim ratios. In Article 3, it was found that investments in research and development (R&D) and corporate sustainability did not generate a positive impact on the economic performance of companies. Conversely, CAPEX and company size demonstrated a positive relationship with profitability. The regional location in the Triângulo Mineiro and Alto Paranaíba did not significantly influence the innovation levels of the surveyed companies, indicating that regionality was not a determining factor for economic performance and innovation. Adherence of research to the PPGAdm concentration area (Management and Regionality) and research line: The research aims to analyze the impact of corporate and regional characteristics on innovation and financial performance of Brazilian companies, focusing on the Triângulo Mineiro and Alto Paranaíba. Although previous studies have not identified a positive relationship between innovation and financial indicators, this research considered it relevant to explore this relationship in the context of Latin America, Brazil, and the Triângulo Mineiro and Alto Paranaíba Region. Impact and innovative nature of intellectual production: The research stands out by exploring the interactions between important themes, such as corporate sustainability, ESG, R&D expenditure, innovation, and their impact on the economic performance of companies in Latin America, Brazil, and the Triângulo Mineiro and Alto Paranaíba region. Furthermore, the findings and established theoretical connections have the potential to influence the direction of future research, stimulating new investigations and discussions on corporate sustainability, innovation, and economic performance, both at the regional and global levels. Economic, social, and regional impact: contributions: The proposed research on the interaction between sustainability, innovation, and economic performance has a significant impact on regional and social development. By driving local economic growth, it creates sustainable opportunities for employment and business, strengthens innovation ecosystems, and promotes customized solutions for regional challenges. Additionally, by respecting the cultural identity and unique characteristics of each region, it contributes to the advancement of Sustainable Development Goals, especially those related to industry, innovation, and reducing inequalities (SDGs 9 and 10). Regional implications: The research stimulates regional economic growth, generating sustainable opportunities for business and employment, strengthening local innovation ecosystems by attracting investments and talent, and highlighting specific challenges for customized solutions. It promotes environmental sustainability initiatives and innovative practices, respecting the cultural particularities and unique characteristics of each region. Sustainable Development Goals addressed in the research: The proposed thesis seeks to investigate how the interaction between sustainability, innovation, and economic performance can contribute to the advancement of Sustainable Development Goals, especially those related to industry, innovation, infrastructure, and reducing inequalities, addressing SDGs 9 and 10. SDGs 9 aim to promote resilient infrastructure, inclusive industrialization, and sustainable innovation. SDGs 10 aim to reduce economic, social, and political inequalities among groups, ensuring inclusion and opportunities for all.